Isolation and characterization of staphylococcus aureus from village and commercial swine farms environment - Jennifer, Jalan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Staphylococcus aureus is a microorganism that can caused mild infection to human such as bacteremia and pneumonia. Methicillin Resistant Staphylococcus aureus (MRS A) interrupted the association with health care environment; hospital~acquired MRSA (HAMRSA) and Community-acquired MRSA (CA-MRSA). This study was carried out to characterize Staphylococcus aureus strains from two swine farms and their farm's environment. The evaluation methods were used by determining the isolates using catalase test, antibiotic susceptibility testing and multiplex PCR technique. A total of 40 staphylococcal isolates were collected from two different swine farms. Biochemical tests revealed 22 (55%) were gram positive, 16 (40%) were catalase positive and overall 13 out of16 (81.25%) of isolates recorded as >0.2 MAR index. Multiplex PCR amplification was used to further confirmed the nuc gene and mecA gene of S.aureus. Based on the findings, 5 out of 40 (12.5%) isolated samples were detected as nuc gene, while 2 out of 40 (5%) carried mecA gene, but confirmed as not MRSA. The occurrence of antibiotic resistant toward penicillin, methicillin and erythromycin was relatively in commercial farm compared to village farm. In summary, it helps to form baseline data of antibiotic resistant in swine farm environment to control the u~age of antibiotics in animal farm.